2009
DOI: 10.1007/s11664-008-0650-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of n-Type Multiple-Filled Skutterudites

Abstract: Filled skutterudites are prospective intermediate temperature materials for thermoelectric power generation. CoSb 3 -based n-type filled skutterudites have good electrical transport properties with power factor values over 40 lW/cm K 2 at elevated temperatures. Filling multiple fillers into the crystallographic voids of skutterudites would help scatter a broad range of lattice phonons, thus resulting in lower lattice thermal conductivity values. We report the thermoelectric properties of n-type multiple-filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 18 publications
6
31
0
Order By: Relevance
“…[1][2][3] Filled skutterudites have the composition RM 4 X 12 , where R is an alkali-earth or rare-earth element, M is a transition metal such as Fe, Co, Rh, or Ir, and X is composed of a pnicogen element such P, As, or Sb. [4][5][6][7] In contrast to the n-type Co 4 Sb 12 with 72 valence electrons, p-type Fe 4 Sb 12 is unstable because it has only 68 valence electrons, and thus a deficiency of 4 electrons. 8 However, it can be stabilized to R 4+ [Fe 4 Sb 12 ] 4À by filling at the voids in the skutterudite structure with R 4+ ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Filled skutterudites have the composition RM 4 X 12 , where R is an alkali-earth or rare-earth element, M is a transition metal such as Fe, Co, Rh, or Ir, and X is composed of a pnicogen element such P, As, or Sb. [4][5][6][7] In contrast to the n-type Co 4 Sb 12 with 72 valence electrons, p-type Fe 4 Sb 12 is unstable because it has only 68 valence electrons, and thus a deficiency of 4 electrons. 8 However, it can be stabilized to R 4+ [Fe 4 Sb 12 ] 4À by filling at the voids in the skutterudite structure with R 4+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] In contrast to the n-type Co 4 Sb 12 with 72 valence electrons, p-type Fe 4 Sb 12 is unstable because it has only 68 valence electrons, and thus a deficiency of 4 electrons. 8 However, it can be stabilized to R 4+ [Fe 4 Sb 12 ] 4À by filling at the voids in the skutterudite structure with R 4+ ions. Because most alkali-earth and rare-earth elements are divalent or trivalent, RFe 4 Sb 12 should be charge-compensated.…”
Section: Introductionmentioning
confidence: 99%
“…Double filling and triple filling of various guest atoms have since been used as methods of reducing lattice thermal conductivity and are the inspiration for the work presented herein. [6][7][8][9] Progressions are being investigated through a multiple filling process of the skutterudite void spaces, introducing the rattling atoms, or thermal vibrations, causing increased phonon scattering. Single filling [10][11][12] and double filling of the void spaces in the skutterudite material have been proven successful with the elements indium, ytterbium, and cerium (In, Yb, and Ce) from the single filling of In by He 9 Peng's successful attempt at double filling of Yb 0.2 In y Co 4 Sb 12 yielded a reduction in lattice thermal conductivity, due to Yb, in comparison with the single-filled approach as well as an enhancement of electrical conductivity because of an increase in the In content.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice thermal conductivity is reduced in filled skutterudites by the formation of Einstein-like vibrational modes arising due to the weak bonding between fillers and Sb atoms of skutterudite framework, thereby scattering the normal phonon modes of the structure having similar energies [77,103]. The vibrational frequencies depend on the type of fillers in the cages and it was found that the rare-earth metals possess weakest vibrational frequencies followed by the alkalineearth metals which yield medium frequencies and the highest vibrational frequencies are maintained by alkali metals [104]. By introducing filler atoms in the cages, lattice thermal conductivity is reduced and this reduction can further be increased by adding two or more filler atoms of different vibrational frequencies which will help in the significant increase of zT like in multi filled skutterudites Ba 0.08 La 0.05 Yb 0.04 Co 4 Sb 12 with the enhanced zT of 1.7 at 577°C [105].…”
Section: Skutteruditesmentioning
confidence: 99%